The bridge kingdom ebook - Jensen, Danielle L. (The Bridge Kingdom, 2019)
The iconic Bridge Kingdom series begins: a sweeping, sizzling fantasy romance filled with political intrigue and passionate love, from the New York Times bestselling author of A Fate Inked in Blood . "Heart-pounding romance and intense action wrapped in a spellbinding world. I was hooked from the first page!"—Elise Kova, USA Today bestselling author of A Deal with the Elf King A warrior princess trained in isolation, Lara is driven by two certainties. The first is that King Aren of the Bridge Kingdom is her enemy. And the second is that she'll be the one to bring him to his knees. The only route through a storm-ravaged world, the Bridge Kingdom enriches itself and deprives its rivals, including Lara's homeland. So when she's sent as a bride under the guise of peace, Lara is prepared to do whatever it takes to fracture its impenetrable defenses. And the defenses of its king. Yet as she infiltrates her new home and gains a deeper understanding of the war to possess the bridge, Lara begins to question whether she's the hero or the villain. And as her feelings for Aren transform from frosty hostility to fierce passion, Lara must choose which kingdom she'll save . . . and which kingdom she'll destroy. Don’t miss any of Danielle L. Jensen's Bridge Kingdom series: THE BRIDGE KINGDOM • THE TRAITOR QUEEN • THE INADEQUATE HEIR • THE ENDLESS WAR • THE TWISTED THRONE (April 8, 2025)